Epigenetic Clocks of Biological Aging and Cognitively Healthy Longevity: The Women’s Health Initiative Memory Study - Andrea Z LaCroix; Bowei Zhang; Steve Nguyen; Susan M Resnick; Luigi Ferrucci; Steve Horvath; Ake T Lu; Mark A Espeland; Stephen R Rapp; Kenneth Beckman; Caroline Nievergelt; Adam X Maihofer; et al. (The Journals of Gerontology, Series A: Biological Sciences and Medical Sciences, 2026)
Abstract BACKGROUND Little is known about whether epigenetic age acceleration (EAA) clocks are capable of predicting exceptional longevity with or without preserved cognitive function. METHODS We examined 5844 women from the Women’s Health Initiative Memory Study. Fifteen epigenetic clocks were measured at baseline (1996-1999). Longevity outcomes were defined as: 1) survival to age 90 with preserved cognition (n = 1726, 29.5%); or 2) survival to age 90 with cognitive impairment (n = 956, 16.4%); vs. 3) death before age 90 (n = 2611, 44.7%). Logistic regression models examined associations between the 15 clocks and survival to age 90 (vs. death before age 90), adjusting for covariates. Multinomial logistic regression models examined associations with survival to age 90 without cognitive impairment and survival to age 90 with cognitive impairment (each vs. death before age 90), also adjusting for covariates. RESULTS Each standard deviation increase in EAA for the first-generation clocks was associated with 7%-18% reduced odds of survival to age 90 vs. earlier death. Stronger associations were observed for second- and third-generation clocks, including AgeAccelGrim2 (OR = 0.66; 95% CI 0.61-0.71), PCGrimAge (OR = 0.64; 95% CI 0.59-0.69), PCPhenoAge (OR = 0.73; 95% CI 0.68-0.78) and DunedinPACE (OR = 0.77; 95% CI 0.72-0.82). None of the clocks was more strongly associated with survival to age 90 with preserved cognition than with survival to age 90 with cognitive impairment, relative to death before age 90. CONCLUSION All epigenetic clocks were associated with exceptional longevity, but none were associated with cognitive healthspan. Developing clocks that can differentiate long survival with and without preserved cognitive function is critical.